Preliminary findings on the commute travel implications of stated preference female teleworkers in Kuala Lumpur - Mustafa, Mootaz Munjid; Kadar Hamsa, Abdul Azeez (2013)
Teleworking has been recognized and promoted as one of the number of strategies for alleviating traffic congestion in urban areas, especially reducing rush-hour traffic. Substantial evidences in the literature suggest that teleworking is more suited to women who when compared to men, experience more work/non-work role conflict and more career interruptions. It is the purpose of this paper to verify and explore the commute travel implications of potential female telecommuters in Kuala Lumpur. Preliminary data analysis indicated an average saving of 312 vehicle-kilometers per teleworker per month as a result of teleworking, and an overall reduction of more than 160,000 commute trips per month. The financial burden of setting up a home office seems to be the biggest barrier preventing the propagation of teleworking among female employees in Kuala Lumpur.